Fads and Fashions - White, John (Canadian Journal of Counselling and Psychotherapy, 2012)
The folly of clambering onto fashionable counselling bandwagons is challenged. The author discusses the question of whether family therapy is a counselling fad. He points out that human beings alienated from families are not sub-human, and that total humanity must include man's existential need for meaning in life, his need for an answer to true guilt, and his growing fascination with mystery and magic.